Diagnosa, Analisis dan Identifikasi Parasit yang Menyerang Ikan Nila (Oreochromis Niloticus) Pada Kawasan Budidaya Ikan Di Subak â€œBaruâ€ Tabanan - I Kadek Adi Wirawan; Sang Ayu Made Putri Suryani; I Wayan Arya (GEMA AGRO, 2018)
Fish cultivation business is one of the very promising business with the increasingly cheap demand of fishery products in the community. So is the case with the cultivation of Tilapia fish. Aquaculture is not spared from various obstacles and problems that often hamper fish farming is the occurrence of disease attacks. Tilapia fish Who was attacked The disease starts with by showing signs of behavioral changes. In addition to the behavior, tilapia also experience a change in color that looks very clear difference compared to fish that are still healthy. Calculation of condition factors, from the three sampling sites average fish is in poor condition indicating that most of fish in pond cultivation have decreased condition that reach 60-90%, caused by disease / phatogen factor or environmental factor not good.The results of the laboratory analysis found six (6) parasites that infect tilapia: Dactyloyrus sp, Gyrodactylus spp, Tricodina sp, Vortycella sp, Oodinium sp, and Saprolegnia sp. Water quality is less good in the cultivation are resulted in the decreased condition of fish and support well the development of various types of parasites.